PENGGUNAAN KLAUSA RELATIF DALAM ARTIKEL “RAGAM PERMAINAN DALAM PEMBELAJARAN BERBICARA BIPA” OLEH RENI ARTANA - Shafariana Shafariana (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This qualitative descriptive research focuses on relative clauses found in the functions of subject, predicate, and object. Relative clauses from "Ragama Permainan dalam Pembelajaran Berbicara BIPA" by Reni Artyana served as the research's source of data. The scientific article by Reni Artyana titled "Ragam Permainan dalam Pembelajaran Berbicara BIPA" that was published online at the ASILE 2014 Conference with a total of 42 pages serves as the research's data source. Reading and taking notes were used as the primary data collection methods. The data were analyzed using qualitative descriptive analysis, involving data reduction (selection, numbering labels, sorting by focus, and grouping by attributes), data presentation, and formulation of conclusions. The findings of this study are as follows: (1) Of the 40 data, 33 were identified as relative clauses with relativized subject positions. Six different clause patterns are used when using relative clauses: S-P-O, S-P-K, S-P, S-P-Pel, S-P-O-Pel, and S-P-O-K. The application of relative clauses with the S-P-O clause pattern, which relativizes the subject position, was discovered in 8 data, the S-P-K pattern in 9 data, the S-P pattern in 9 data, the S-P-Pel pattern in 2 data, the S-P-O-Pel pattern in 2 data, and the S-P-O-K pattern in 3 data; (2) none of the 40 data were classified as relative clauses with relativized predicate position. There were 2 data that seemed to be relative clauses but weren't; and (3) out of 40 data, 5 were classified as relative clauses with relativized object position. The use of relative clauses has six variations of clause patterns, namely S-P-O (3 data), S-P-Pel (1 data), and S-P-Pel-K (1 data).